Analysis of images, social networks and texts : 8th International Conference, AIST 2019, Kazan, Russia, July 17-19, 2019, Revised Selected Papers /: 8th International Conference, AIST 2019, Kazan, Russia, July 17-19, 2019, Revised Selected Papers. (2019) - Unknown
No abstract available